2017
DOI: 10.1111/mpp.12617
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of copine genes confers common wheat enhanced resistance to powdery mildew

Abstract: Powdery mildew, caused by the biotrophic fungal pathogen Blumeria graminis f. sp. tritici (Bgt), is a major threat to the production of wheat (Triticum aestivum). It is of great importance to identify new resistance genes for the generation of Bgt-resistant or Bgt-tolerant wheat varieties. Here, we show that the wheat copine genes TaBON1 and TaBON3 negatively regulate wheat disease resistance to Bgt. Two copies of TaBON1 and three copies of TaBON3, located on chromosomes 6AS, 6BL, 1AL, 1BL and 1DL, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…The field trials in this study support some investigations conducted in controlled conditions where plant responses to obligate pathogens were either independent of resistance genes and determined with temperature changes 25 or influenced by calcium-dependent phospholipid-binding proteins responsive to both pathogen infection and temperature changes 26 . The results of this study showed that in agro-ecological conditions in Serbia, high temperatures in February could initiate a predominance of yellow rust in a greater number of winter wheat genotypes compared to the number of genotypes in the year when high winter temperatures are met only in January.…”
Section: Discussionsupporting
confidence: 78%
“…The field trials in this study support some investigations conducted in controlled conditions where plant responses to obligate pathogens were either independent of resistance genes and determined with temperature changes 25 or influenced by calcium-dependent phospholipid-binding proteins responsive to both pathogen infection and temperature changes 26 . The results of this study showed that in agro-ecological conditions in Serbia, high temperatures in February could initiate a predominance of yellow rust in a greater number of winter wheat genotypes compared to the number of genotypes in the year when high winter temperatures are met only in January.…”
Section: Discussionsupporting
confidence: 78%
“…These results indicate that TaPT29-6A silencing weakens resistance to powdery mildew caused by Bgt . To examine whether silencing TaPHT1 could affect the expression levels of defense response genes, TaPR4A/B [45,46] and TaPR2/10 [72,73] were chosen as marker genes for defense responses to necrotrophic and biotrophic pathogens. In addition, qRT-PCR analysis showed that transcript levels of the TaPR4A/B and TaPR2/10 marker genes for defense responses to necrotrophic and biotrophic pathogens were significantly lower in the TaPT29-6A -silenced plants than in the controls (Figure 9D), in accordance with the susceptible phenotypes of VIGS plants.…”
Section: Resultsmentioning
confidence: 99%
“…Common wheat provides dietary carbohydrates for more than one-third of the population in the world ( Zou et al, 2018 ). Production of wheat is critical for global food security, but its grain yield and quality are negatively affected by various pathogens.…”
Section: Introductionmentioning
confidence: 99%